Comparative Analysis of Classical and Deep Algorithms for Text Clustering in Brazilian Portuguese - Mourão, Paulo V.; Pessoa, Marcela P.; Ekwoge, Oswald M.; Anjos, Marcelo E. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
This work compares different combinations of text embedding models and clustering algorithms applied to Portuguese-language texts. Three datasets were used (poems, Reddit, and product reviews), evaluating models such as BERTimbau and ST5, combined with classic algorithms and the deep method DEC. Using accuracy, V-Measure, and ARI as metrics, results show that BERTimbau performs better on formal texts, while ST5 excels in informal content. DEC outperformed others only on the largest dataset (product reviews), highlighting the potential of deep clustering approaches for Portuguese text analysis.